Treadmill Exercise during Pregnancy Decreased Vulnerability to Neonatal Hypoxia-Ischemia through Reducing Inflammation and Increasing Antiapoptotic Gene Expressions and Antioxidant Capacity in Rats - Elahe Gorgij; Hamed Fanaei; Parichehr Yaghmaei; Mohammad Reza Shahraki; Hadi Mirahmadi (Stroke Research and Treatment)
Background. The purpose of present study was to assess the impact of maternal treadmill exercise during pregnancy on inflammation, oxidative stress, expression of Bax and Bcl-2 genes, and brain-derived neurotrophic factor (BDNF) level in neonatal rat brain after the hypoxia-ischemia injury. Material and Methods. A total of 24 female Wistar rats were utilized in this research. Two groups are randomly considered for rats: (1) not exercised through pregnancy and (2) exercised during pregnancy. Offsprings were divided into four groups including after delivery: (1) sham, (2) sham/exercise (sham/EX), (3) HI, and (4) HI+exercise. HI was induced in pups at postnatal day 8. Neurobehavioral tests were done seven days after HI induction. Then, the brain tissue was taken from the skull to estimate Bcl-2 and Bax gene expressions, BDNF, cerebral edema, infarct volume, inflammatory factors, oxidative stress, and neurological function. Results. The BDNF level in the HI+exercise group was considerably higher than the HI, sham, and sham/EX groups. Tumor necrosis factor (TNF-α), C-reactive protein (CRP), and the whole oxidant capacity (TOC) levels in the HI group were significantly higher than the sham and sham/EX groups. TNF-α, CRP, and TOC levels in the HI+exercise group were significantly lower than the HI group. Total antioxidant capacity (TAC) level in the HI+exercise group was significantly higher than the HI group. Infarct volume and edema percent in the HI+exercise group were significantly lower than the HI group. Neurological function in the HI+exercise group was significantly better than the HI group. Bax expression in the HI+exercise group was significantly lower than the HI group. Bcl-2 expression in the HI+exercise group was significantly higher than the HI group. In the sham group, BDNF, TNF-α, CRP, TAC, TOC, edema levels, and neurological function had no significant difference with the sham/EX group. Conclusion. It appears that the maternal treadmill exercise during pregnancy exerts a supportive impact against neonatal HI brain injury through increasing antioxidant capacity, Bcl-2 expression, and BDNF levels and decreasing inflammation that is resulted in the lower infarct volume and sensorimotor dysfunction.